1997
DOI: 10.1021/je970097d
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of CO2 in Aqueous Methyldiethanolamine Solutions

Abstract: For 5.0, 20.5, 50.0, and 75.0 mass % methyldiethanolamine (MDEA) aqueous solutions, solubilities of CO2 were measured at 323.15, 348.15, and 373.15 K, respectively. Isothermal absorption capacities of CO2 as a function of MDEA concentration are presented. Lastly, the absorption enthalpy of CO2 in 50.0 mass % MDEA solution was calculated to be 54 kJ·mol-1 CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 4 publications
9
65
0
Order By: Relevance
“…7 are the actual data from the literature sources at the measured pressure that was closest to atmospheric pressure. The work by Kierzkowska-Pawlak [31] and Rho et al [34] were compared numerically with our data, since their experimental conditions were similar to ours. Taking into account the differences in pressure and MDEA weight fraction, the maximum deviation in mole fraction between our data and the data by Kierzkowska-Pawlak [31] and Rho et al [34] was 0.0036.…”
Section: Bubbling Apparatussupporting
confidence: 63%
See 1 more Smart Citation
“…7 are the actual data from the literature sources at the measured pressure that was closest to atmospheric pressure. The work by Kierzkowska-Pawlak [31] and Rho et al [34] were compared numerically with our data, since their experimental conditions were similar to ours. Taking into account the differences in pressure and MDEA weight fraction, the maximum deviation in mole fraction between our data and the data by Kierzkowska-Pawlak [31] and Rho et al [34] was 0.0036.…”
Section: Bubbling Apparatussupporting
confidence: 63%
“…Solubility data of CO 2 in aqueous MDEA solutions at atmospheric pressure were found in the work by Kierzkowska-Pawlak [31] and Bhairi [32] with w 3 ≈ 10%, in the work by Kierzkowska-Pawlak [31], Bhairi [32], Ermatchkov et al [33] and Rho et al [34] with w 3 ≈ 20%, and for w 3 ≈ 50% data were found in Ermatchkov et al [33], Rho et al [34], Ma'mun et al [35], Park and Sandall [6], Jou et al [36] and Austgen et al [37]. The mole fractions of CO 2 measured with the bubbling apparatus are compared with the literature data in Fig.…”
Section: Bubbling Apparatusmentioning
confidence: 95%
“…Some researchers have proposed the coupling of two kinds of technologies together for the capture of CO 2 , such as coupling of membrane separation and absorption or adsorption and reaction (Carley et al, 2012;Maslan, 1972;. Absorption separation technology includes both physical absorption, which depends mainly on temperature and pressure, and chemical absorption, which is dependent on an acid-base neutralization reaction (Lee et al, 2008;Lim et al, 2012;Mortazavi-Manesh et al, 2013;Rho et al, 1997;Wang et al, 2013). A new class of solvents for CO 2 capture is ionic liquids (ILs), which have exhibited great potential in the absorption of CO 2 and are environmentally benign due to their unique properties of negligible volatility, high thermal stability, strong solubility capacity, and tunability of molecular structures and physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, among the available amines, N-methyldiethanolamine (MDEA) is noticeable due to some of its unique characteristics like high thermal and chemical stability, low vapour pressure and less corrosive behaviour [15]. Therefore, in the present work, binary mixtures of 1-hexyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate [hmim] [FAP] with Nmethyldiethanolamine (MDEA) were prepared at different mole fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Density q and refractive indices n D for the binary mixtures were measured at different mole fractions and at temperature range of (303. 15 4 ] was determined by using DL-55 autotitrator (Mettler-Toledo) with 0.005 M, AgNO 3 as the titrant. The estimated chloride content was 34 ppm.…”
Section: Introductionmentioning
confidence: 99%